2020
DOI: 10.1080/00220485.2020.1804504
|View full text |Cite
|
Sign up to set email alerts
|

Measuring economic competence of secondary school students in Germany

Abstract: Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden. Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen. Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in der dort genannten Lizenz … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 65 publications
1
9
0
Order By: Relevance
“…We conduct a two-stage sampling procedure (stratified by degree of urbanization) with random selection of schools in the first stage and a random selection of one class per school at baseline (i.e., in 7 th grade) for each cohort. The number of sampled schools is adapted to the proportion of the relevant stratum in the whole population (i.e., the sampling probability is proportional to the size of the strata) (see also Kaiser et al 2020, Oberrauch and and we account for any remaining sample disproportionalities by including design weights defined as the inverse of the selection probability in our analyses. The survey was subsequently administered as a computer-based assessment during the regular school lessons and carefully supervised by the respective teachers.…”
Section: Sampling and Proceduresmentioning
confidence: 99%
“…We conduct a two-stage sampling procedure (stratified by degree of urbanization) with random selection of schools in the first stage and a random selection of one class per school at baseline (i.e., in 7 th grade) for each cohort. The number of sampled schools is adapted to the proportion of the relevant stratum in the whole population (i.e., the sampling probability is proportional to the size of the strata) (see also Kaiser et al 2020, Oberrauch and and we account for any remaining sample disproportionalities by including design weights defined as the inverse of the selection probability in our analyses. The survey was subsequently administered as a computer-based assessment during the regular school lessons and carefully supervised by the respective teachers.…”
Section: Sampling and Proceduresmentioning
confidence: 99%
“…In both the US and Germany, gender has correlated with students' economic knowledge (for the US, see Asarta et al 2014; for Germany, see Förster and Happ 2019;Kaiser et al 2020). In most studies of economic knowledge, a gender gap favoring male students has been found (for the US, see Bayer and Wilcox 2019; for Germany, see Kaiser et al 2020;Jüttler and Schumann 2019;Schlax et al 2020).…”
Section: Economic Knowledgementioning
confidence: 99%
“…In the literature, gender (Asarta et al 2014;Jackstadt and Grootaert 1980;Walstad and Robson 1997) and primary language (Walstad et al 2013) are repeatedly discussed as important factors influencing students' acquisition of economic knowledge in the US. These two personal characteristics are also discussed as relevant determinants of students' economic knowledge in Germany (Kaiser et al 2020;Schlax et al 2020). Although in some studies conducted at the college level a comparable test of economic knowledge has been employed in the US and Germany (Brückner et al 2015), no study has been conducted at the secondary school level using an adapted and, therefore, comparable test to analyze the influence of the two characteristics in both countries.…”
Section: Introductionmentioning
confidence: 99%
“…In almost all studies, male subjects also perform better than their female colleagues (e.g. Beck, 1993;Förster and Happ, 2019;Gill and Gratton-Lavoie, 2011;Jüttler and Schumann, 2019;Kaiser et al, 2020;Kotte and Lietz, 1998;Lüdecke-Plümer and Sczesny, 1998;Müller et al, 2007;Schmidt et al, 2016;Soper and Walstad, 1987). One of the reasons for this can be attributed to the often-found gender-related differences in interest in economics (Beck and Wuttke, 2004;Ackermann and Siegfried, 2019;Förster and Happ, 2019;Jüttler and Schumann, 2019).…”
Section: Economic Competence and Individual Influencing Factorsmentioning
confidence: 99%